NOX4 modulates breast cancer progression through cancer cell metabolic reprogramming and CD8+ T cell antitumor activity - Xiong, Yingying; Weng, Yiming; Zhu, Shan; Qin, Jian; Feng, Jia; Jing, Xiaopeng; Luo, Chao; Gong, Wei; Sun, Rui; Peng, Min (Frontiers in Immunology, 2025)
IntroductionBreast cancer is the most frequently diagnosed malignancy and a leading cause of cancer-related mortality among women worldwide. Although NADPH oxidase 4 (NOX4) has been implicated in various oncogenic processes, its exact function in breast cancer progression, metabolic reprogramming, and immune modulation remains unclear.MethodsWe used murine 4T1 and EO771 breast cancer models to generate NOX4 knockout (KO) cell lines via CRISPR/Cas9. In vitro assays (cell proliferation, colony formation, wound healing, and Seahorse metabolic analyses) and in vivo orthotopic tumor studies assessed the impact of NOX4 loss. Transcriptomic changes were identified through RNA sequencing and gene set enrichment analysis. We performed MYC knockdown in NOX4 KO cells to investigate its mechanistic role. Flow cytometry characterized tumor-infiltrating immune cells. Finally, NOX4-overexpressing cells were tested for survival benefit and response to dual-checkpoint immunotherapy (anti-PD-1/anti-CTLA-4).ResultsNOX4 deletion accelerated tumor growth in vivo and enhanced proliferation, colony formation, and migratory capacity in vitro. Metabolic profiling showed that NOX4 KO cells had elevated glycolysis and fatty acid oxidation, along with increased mitochondrial mass. Transcriptomic and enrichment analyses revealed MYC pathway activation in NOX4 KO cells; suppressing MYC reversed these hyperproliferative and metabolic changes. Immunologically, NOX4 KO reduced CD8+ T cell infiltration and function, partially due to lowered CCL11/CCL5 levels, while PD-L1 expression was upregulated. In contrast, NOX4 overexpression improved survival in mice and synergized with checkpoint blockade, demonstrating a positive effect on anti-tumor immunity.DiscussionThese findings show that NOX4 constrains breast cancer aggressiveness by limiting MYC-driven metabolic adaptations and supporting CD8+ T cell-mediated immunity. Loss of NOX4 promotes a more malignant phenotype and dampens T cell responses, whereas its overexpression prolongs survival and enhances checkpoint inhibitor efficacy. Therapeutically targeting the NOX4–MYC axis and leveraging NOX4’s immunomodulatory capacity could offer promising strategies for breast cancer management.